Effect of Variable Apodization Functions on the Image Quality of Optical System - Kaesar Abdul Hassan Abbas; Ghada Sabah Karam; Ziad M. Abood (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Apodization of pupil with various amplitude filters have been investigated for altering the point spread function for diffraction-limited optical systems’ pictures of point objects by employing various filters, such as connes and tringle filters. We have shown that, for different levels of amplitude apodization, the lower values. An observation that these filters give good results for lower values of the apodization parameter. (FWHM) Full width at half maximum of the point spread function (PSF) is smaller than the Airy PSF, improving the performance of the optical system.